Upregulation of Caveolae-Associated Proteins in Lesional Samples of Hidradenitis Suppurativa: A Case Series Study - Neil Seth; Beatriz Abdo Abujamra; Maria Boulina; Hadar Lev-Tov; Ivan Jozic (Elsevier, 2023)
Hidradenitis suppurativa (HS) is a chronic, inflammatory skin condition. HS disease management has proven difficult owing to an insufficient understanding of the immunological processes that drive its pathogenesis. We have demonstrated that misregulation of caveolae perturbs inflammatory responses, inhibits cutaneous wound healing, and contributes to immune privilege collapse in other hair follicle-related diseases. However, nothing is known about its role or the role of structural components of caveolae (caveolin [Cav1] 1, Cav2, and Cavin-1) in the pathophysiology of HS. We aimed to identify whether Cav1, Cav2, and Cavin-1 may serve as immunohistochemical markers of HS. Lesional and perilesional HS skin samples from patients (n = 7, mean age = 35.7 years, range = 20-57 years) with active HS and normal skin from control participants (n = 4, mean age = 36.7 years, range = 23-49 years) were used to assess Cav1, Cav2, and Cavin-1 expression and localization by immunofluorescence staining. HS samples demonstrated increased levels of Cav1 compared with normal skin, whereas Cav1, Cav2, and Cavin-1 were all elevated in hair follicles of lesional versus perilesional HS samples, suggesting a potentially novel therapeutic target and highlighting caveolae as potential biomarkers of HS.